2015
DOI: 10.1086/682389
|View full text |Cite
|
Sign up to set email alerts
|

Legislative Bargaining with Endogenous Rules

Abstract: We study repeated legislative bargaining in an assembly that chooses its bargaining rules endogenously, and whose members face an election after each legislative term. An agenda protocol or bargaining rule assigns to each legislator a probability of being recognized to make a policy proposal in the assembly. We predict that the agenda protocol chosen in equilibrium disproportionately favors more senior legislators, granting them greater opportunities to make policy proposals, and it generates an incumbency adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In Diermeier et al (2015) and Diermeier et al (2016), the recognition probabilities are determined through bargaining before bargaining over policy takes place. In McKelvey & Riezman (1992), McKelvey & Riezman (1993), Muthoo & Shepsle (2014) and Eguia & Shepsle (2015), recognition probabilities are determined through seniority which is endogenously determined through elections at the end of each legislative session. Cardona & Polanski (2013) study the effects of the voting quota on the social cost of rentseeking in a spatial bargaining model.…”
Section: Endogeneous Proposer Selection Rulesmentioning
confidence: 99%
“…In Diermeier et al (2015) and Diermeier et al (2016), the recognition probabilities are determined through bargaining before bargaining over policy takes place. In McKelvey & Riezman (1992), McKelvey & Riezman (1993), Muthoo & Shepsle (2014) and Eguia & Shepsle (2015), recognition probabilities are determined through seniority which is endogenously determined through elections at the end of each legislative session. Cardona & Polanski (2013) study the effects of the voting quota on the social cost of rentseeking in a spatial bargaining model.…”
Section: Endogeneous Proposer Selection Rulesmentioning
confidence: 99%
“…A natural way of determining the party leadership is to employ some form of a seniority system. This suggests that it would be worthwhile to consider a repeated game version of our model in which seniority can play a substantive role, as it does in the legislative bargaining models of McKelvey and Riezman (1992, 1993), Muthoo and Shepsle (2014), and Eguia and Shepsle (2015).…”
Section: Discussionmentioning
confidence: 99%
“…McKelvey and Riezman (1992, 1993), Muthoo and Shepsle (2014), Eguia and Shepsle (2015), and Jeon (2015) all considered repeated versions of a divide-the-dollar game in which the recognition probabilities evolve over time. In the case of McKelvey and Riezman (1992, 1993), Muthoo and Shepsle (2014), and Eguia and Shepsle (2015), legislators agree to implement a seniority system whose recognition probabilities depend on relative seniority. In the case of Jeon (2015), a legislator’s recognition probability is an increasing function of his previous period’s share of the dollar.…”
Section: Related Literaturementioning
confidence: 99%
“…However, rational prospective voters must evaluate the value of re-electing an incumbent versus replacing him with a new politician. Scholars have nevertheless shown that an incumbency advantage can emerge due to noisy signaling by incumbents using messages that are payoff irrelevant to voters (Caselli, Cunningham, Morelli and Moreno de Barreda, 2014), voters imperfectly observing previous electoral margins (Fowler, 2018), or learning by doing (Dick and Lott, 1993) and legislative seniority rules (Muthoo and Shepsle, 2014;Eguia and Shepsle, 2015). Incumbency disadvantage can emerge when a politician's ability to secure personal rents increases with tenure (Klašnja, 2016).…”
mentioning
confidence: 99%
“…The crux of our theory is a decline in the effects of accountability over a politician's tenure in office; this decline may owe to either the politician's political horizon (under term limits, as in Sections 1-2) or from the electorate's information (when type is revealed in office, as in Section 3). One can view our theory as combining this decline with the nature of reputation effects to offer a unified microfoundation for why politicians may become more effective (Dick and Lott, 1993;Muthoo and Shepsle, 2014;Eguia and Shepsle, 2015) or more corrupt (Klašnja, 2016) over their career; the former emerges under bad reputation effects while the latter emerges under good reputation effects.…”
mentioning
confidence: 99%